A novel method for determining the degree of hydrogen loading of LOHC using cavity based permittivity measurements - Weiss, Nico; Koelpin, Alexander; Wiemann, Irina; Schlücker, Eberhard (2023 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2023, 2023)
Liquid organic hydrogen carriers are a promising candidate to reduce the risk of handling hydrogen. However, the determination of their hydrogenation is still the subject of research. In this paper, a novel method for measuring hydrogen loading based on the permittivity of the hydrogen carriers used is presented. The cavity resonator developed for this application is shown and the design decisions made as well as the processing required are explained. Finally, the results of the test measurements are presented and discussed.
CRIS-Team Scopus Importer:2023-03-17
Keywords: cavity; measurment; permittivity